PENGARUH PENAMBAHAN LEVEL MOLASES TERHADAP KUALITAS FISIK DAN ORGANOLEPTIK PELLET PAKAN KAMBING PERIODE PENGGEMUKAN - Risti Sstyaning Ismi; Retno Iswarin Pujaningsih; Sri Sumarsih (JURNAL ILMIAH PETERNAKAN TERPADU, 2017)
PENGARUH PENAMBAHAN LEVEL MOLASES TERHADAP KUALITAS  FISIK DAN ORGANOLEPTIK PELLET PAKAN KAMBING PERIODE PENGGEMUKAN The Effect of Molases Level Addition on Physical and Organoleptic Quality of Goat Feed Pellets on Fattening Period Risti Sstyaning Ismi, Retno Iswarin Pujaningsih, dan Sri Sumarsih Faculty of Animal and Agriculture Science, Diponegoro UniversityProf. H. Soedarto, S.H., Tembalang, Semarang, Indonesiae-mail : ristisatya357@gmail.com  ABSTRACT The aim of this research is to study the effect of molasses level increase on physical quality and organoleptic of fattening period goat feed in pellet form. Material used in the research is rice bran, cassava peel, elephant grass, tofu waste product, molasses and premix. Completely randomized design was used in a study with 4 replications and 4 treatments, T0 = pellet ration + 0% molases, T1 = pellet ration + 3% molases, T2 = pellet ration + 5% molases, and T3 = pellet ration + 7% molases. Parameters observed were hardness, durability, color, texture and pellet scent. The results showed that the addition of molasses level had significant effect (P<0,05) on the improvement of physical quality of pellet and the decreasement of pellet organoleptic quality. Pellet with the addition of molasses as much as 3% has the best physical and organoleptic quality. Research conclusions recommended that the addition of molasses up to level 3% can provide good effect for the physical quality and organoleptic pellet. Keywords : Molasses Level, Pellet, Physical Quality, Organoleptic Quality.